Adaptation of foreign technologies of intensive cultivation of scots pine planting material in Kazakhstan - Svetlana Anatolyevna Kabanova; Valery Anatolyevich Bortsov; Matvey Anatolyevich Danchenko (RUDN Journal of Agronomy and Animal Industries, 2020)
The purpose of the research was the adaptation of foreign technologies for intensive and accelerated cultivation of Scots pine planting material in Kazakhstan. Objects of research were annual seedlings of scots pine in forest nurseries of Pavlodar, Akmola, and North Kazakhstan regions. The experiments were established in 4 directions: application of dry growth regulators to soil, pre-sowing seed treatment with growth regulators, soaking seeds in stimulants and fungicide, pre-sowing watering of the soil with growth regulators. It was established that seed quality decreased significantly compared to the last year, only seeds from Pavlodar region had high indicators. Seeds from the nursery ‘Ertic Ormany’ had the highest average indicators of soil germination (58.7…67.8%). In ‘Bukhpa’, the highest germination was observed in seeds soaked with Zircon + Trichocin (3 + 2 hours). Baikal growth regulator and AridGrow slightly increased germination in the nursery of Arykbalyk branch of ‘Kokshetau’. In the forest nursery ‘Ertis Ormany’, the highest annual seedlings were obtained in variants with presowing treatment of scots pine seeds with stimulants and watering the soil with growth substances. The average height of experimental seedlings was 4.32 and 4.64 cm, respectively. The combined use of Zircon and Trichocin increased seedling growth in ‘Bukpa’ nursery to 1.42 cm, which was the highest value. It was revealed that the technologies used in neighboring countries for intensive cultivation of scots pine seedlings showed a positive effect only when using Citovit. According to other experiments, it was determined that seedlings of scots pine grown from seeds with pre-sowing treatment in Gumat+7 for 12 hours had the best growth indicators in height. Increased soil fertility through applying nitrogen, phosphorus fertilizers, soil activator AridGrow and KZ Cultury significantly accelerated growth of scots pine seedlings.